Work-related musculoskeletal disorders and associated factors among bank workers in Addis Ababa, Ethiopia: a cross-sectional study - Dereje Dagne; Solomon Mekonnen Abebe; Atalay Getachew (Komiyama Printing Co. Ltd, 2020)
Abstract Background Work-related musculoskeletal disorders (WMSDs) are dramatically increased in the world due to the advancement of technology and competitiveness of markets. There were limited studies carried out regarding WMSDs among bank workers in Africa particularly in Ethiopia. Therefore, the aim of this study was to assess the magnitude of work-related musculoskeletal disorders and associated factors among bank workers in Addis Ababa, Ethiopia. Methods Institution-based cross-sectional study design was employed in the study. Multi-stage sampling techniques were used to select 838 bank workers from 62 banks in Addis Ababa. Self-administered standard Nordic questionnaires were used as well. Multivariable binary logistic regression analyses were employed to identify factors associated with WMSDs. Moreover adjusted odds ratio (AOR), 95% confidence interval (CI) and p value < 0.05 was used to show the strength of association between explanatory variables and dependent variable. Results Out of 838 total numbers of participants, 755 bank workers returned their questionnaires responding with a rate of 90%. Of these, 77.6% (N = 586) suffered WMSDs with a 95% CI [75-81%]. Based on the final multivariate logistic regression analysis being female [AOR = 2.98, 95% CI 1.91-4.65], sitting back in a twisted position [AOR = 3.59, 95% CI 2.13-6.08], sitting back bent [AOR = 4.06, 95% CI 2.48-6.66], work on fixed position [AOR = 1.78, 95% CI 1.17-2.71], no work time break [AOR = 3.33, 95% CI 1.44-7.71], type of chairs [AOR = 2.62, 95% CI 1.19-5.75] and job stress [AOR = 2.33, 95% CI 1.19-4.54] were factors significantly associated with WMSDs. Conclusion From the study's findings, the magnitude of work-related musculoskeletal disorders among bank workers was high. Being female, awkward posture, no work time break, fixed position, type of chairs, and job stress are the factors significantly associated with WMSDs. So bank workers should use proper types of chairs, practice proper work posture, increase healthy working conditions, and create awareness programs on how to maintain beneficial health conditions which may lead to increased leisure time.